Understanding of chemical labeling using Globally Harmonised System (GHS) amongst students of secondary level in Terengganu, Malaysia - Syed Draman, Sarifah Fauziah; Daik, Rusli; Jusoff, Kamaruzaman; Abdullah, Mohd Lazim (IDOSI Publications, 2010)
Chemical substances can be handled safely if properties of the chemical substances are wholly understood and properly managed. From our observation, students at tertiary level in college or university still cannot handle chemical substances correctly due limitation of their knowledge and training. In Malaysia students start to deal with chemical substances since primary level but they usually handle chemical substances themselves including hazardous substances at secondry level when doing laboratory activities. Therefore, understanding on classification and labeling of chemicals for secondry level students was studied. Globally Harmonized Systems (GHS)is chosen because this system is expected to be adopted internationally and will replace the relevant laws and regulations used in different countries with worldwide toward implementation started in 2008. Methodology for this study is descriptive quantitative survey. Cluster probability sampling was used for secondary levels students in Terengganu. Results of this study shows that the secondary levels students cannot recognize chemical substance label correctly by using GHS. The understanding would influence attitude, which may futher affect the behaviour while handling chemical substances. Therefore, it is suggested to revise teh chemistry curriculum for secondary level schools in which the hazard communication based on GHS should be incorporated.